Beware of Misdelivery: Multifaceted Role of Retromer Transport in Neurodegenerative Diseases - Yoshida, Shun; Hasegawa, Takafumi (Frontiers in Aging Neuroscience, 2022)
Retromer is a highly integrated multimeric protein complex that mediates retrograde cargo sorting from endosomal compartments. In concert with its accessory proteins, the retromer drives packaged cargoes to tubular and vesicular structures, thereby transferring them to the trans-Golgi network or to the plasma membrane. In addition to the endosomal trafficking, the retromer machinery participates in mitochondrial dynamics and autophagic processes and thus contributes to cellular homeostasis. The retromer components and their associated molecules are expressed in different types of cells including neurons and glial cells, and accumulating evidence from genetic and biochemical studies suggests that retromer dysfunction is profoundly involved in the pathogenesis of neurodegenerative diseases including Alzheimer’s Disease and Parkinson’s disease. Moreover, targeting retromer components could alleviate the neurodegenerative process, suggesting that the retromer complex may serve as a promising therapeutic target. In this review, we will provide the latest insight into the regulatory mechanisms of retromer and discuss how its dysfunction influences the pathological process leading to neurodegeneration.